Homometallic DyIII Complexes of Varying Nuclearity from 2 to 21: Synthesis, Structure, and Magnetism. Issue 21 (27th March 2017) - Biswas, Sourav; Das, Sourav; Acharya, Joydev; Kumar, Vierandra; van Leusen, Jan; Kögerler, Paul; Herrera, Juan Manuel; Colacio, Enrique; Chandrasekhar, Vadapalli
Abstract: The synthesis, structure, and magnetic properties of four Dy III coordination compounds isolated as [Dy2 (LH2 )2 (μ2 ‐η 1 :η 1 ‐Piv)]Cl⋅ 2 MeOH⋅ H2 O (1 ), [Dy4 (LH)2 (μ3 ‐OH)2 (Piv)4 (MeOH)2 ]⋅ 4 MeOH⋅ 2 H2 O (2 ), [Dy6 (LH2 )3 (tfa)3 (O3 P t Bu)(Cl)3 ]Cl4 ⋅ 15.5 H2 O⋅ 4 MeOH⋅ 5 CHCl3 (3 ) and [Dy21 (L)7 (LH)7 (tfa)7 ]Cl7 ⋅ 15 H2 O⋅ 7 MeOH⋅ 12 CHCl3 (4 ) are reported (Piv=pivalate, tfa=1, 1, 1‐trifluoroacetylacetone, O3 P t Bu= tert ‐butylphosphonate). Among these, 3 displays an equilateral triangle topology with a side length of 9.541 Å and a rare pentagonal‐bipyramidal Dy 3+ environment, whereas complex4 exhibits a single‐stranded nanowheel structure with the highest nuclearity known for a homometallic lanthanide cluster structure. A tentative model of the dc magnetic susceptibility and the low‐temperature magnetization of compounds1 and2 indicates that the former exhibits weak ferromagnetic intramolecular exchange interaction between the Dy 3+ ions, whereas in the latter both intramolecular ferromagnetic and antiferromagnetic magnetic exchange interactions are present. Compounds1, 3, and4 exhibit frequency‐dependent ac signals below 15 K at zero bias field, but without exhibiting any maximum above 2 K at frequencies up to 1400 Hz. The observed slow relaxation of the magnetization suggests that these compounds could exhibit single molecule magnet (SMM) behavior with either a thermal energy barrier for the reversal of the magnetization that is not high enough to block the magnetization above 2 K, or there exists quantum tunneling of the magnetization (QTM). Abstract : It′s complex : Utilization of a multidentate flexible aroyl hydrazine‐based Schiff base ligand, 6‐((bis(2‐hydroxyethyl)amino)methyl)‐ N ′‐((8‐hydroxyquinolin‐2‐yl)methylene)picolinohydrazide leads to formation of four complexes with Dy2 , Dy4 , Dy6 , and Dy21 metallic cores. Nuclearity is controlled by the successive deprotonation of the ligand in combination with judicious choice of co‐ligands. Detailed static and dynamic magnetic properties of all the complexes reveal SMM characteristics for the Dy2 , Dy6 , and Dy21 complexes.